(untitled) (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2023)
Creative Innovation in teaching significantly impacts EFL students’ success. This research explored teachers’ teaching methods in an Indonesian English immersive Environment. It was a qualitative study that involved eight participants. The research was conducted in a "Let’s Speak class" at Mr. Pepsi Upgrade English Institution in Kampung Inggris Pare, Kediri. Data were collected from classroom observation, interviews, photos, and documents. Then, the data were analyzed in six steps, from preparing to interpreting the description of the data’s meaning. Research findings presented that teacher in Indonesian immersive environments taught English, especially for communicative instruction, utilizing technology, such as communicative instruction based on a listening approach. It was called a Listening-based Communicative Instructional Approach model (L-CIA model). Six phases were trained, from giving ice-breaking preface and chitchat, listening to a song and filling in the blank, finding problematic words and translating, explaining the song using own words, and singing together. This method has been proven to stimulate the students’ speaking skills. Finally, this research contributed to sharing information about teaching Innovation in Second Language Acquisition in the Indonesian Immersive Environment, which can be implemented in other contexts.